The socio-demographic and clinical factors associated with quality of life among patients with haematological cancer in a large government hospital in Malaysia. - Das, Priscilla; Awang, Hamidin; Md. Zain, Azhar; Naing @ Noor Jan, Khin Ohnmar; Md. Said, Salmiah; Khalid, Bahariah (Universiti Sains Malaysia, 2011)
Background: The paper examined the quality of life of haematological cancer patients according to their socio-demographic profiles and clinical diagnoses. Methods: This cross-sectional study was conducted at the tertiary referral centre of Ampang Hospital, Kuala Lumpur, involving 105 patients. The European Organisation for Research and Treatment of Cancer Quality of Life (EORTC QLQ-C30) questionnaire was used to measure their quality of life. Results: The study involved patients diagnosed with all types of haematological cancer, including non-Hodgkin lymphoma (NHL), acute myelogenous leukaemia (AML), acute lymphoblastic leukaemia (ALL), Hodgkin lymphoma (HL), and multiple myeloma (MM), with a response rate of 83.3%. The patients with ALL, HL, without NHL, and without MM were younger than other patients. There were significant differences in quality of life scores in different socio-demographic groups and types of cancer diagnosis. The global quality of life of the female patients was much better than that of the male patients. Patients who were 40 years old or younger had a better global quality of life and physical functioning, as well as fewer symptoms of constipation, nausea, and vomiting. Employed patients were in less pain but showed greater impairments of cognitive function than did unemployed patients. Patients who earned a monthly wage of RM1000 or less had reduced physical function, more symptoms of pain, and more financial difficulties compared with patients who earned more. Patients with AML tended to have better physical functioning than did patients with MM, whose physical functioning was impaired. Comparatively, more symptoms of dyspnoea were found in ALL and HL patients than in other types of lymphoma. Compared with other patients, those with ALL had a greater loss of appetite, and other lymphoma patients had fewer symptoms of pain. Patients with NHL had impaired role functioning and more constipation compared with other patients. The results were all statistically significant (P < 0.05). Conclusion: The quality of life of haematological cancer patients is affected by sociodemographic factors and clinical diagnoses. Efforts should be made to improve the overall quality of life of these patients.